Installing, maintaining, and publishing Node modules with npm - Powers, Shelley (O'Reilly Media, Inc., 2016)
The Node package manager, npm, is an essential tool and part of any Node workflow. This lesson covers how to install npm, and how to use it to install Node modules locally and globally. You'll also learn how to search for existing Node modules and create and publish your own modules. Why is it important? For anyone using Node, npm is absolutely essential. It's critical to understand how to use it, and how npm manages modules and dependencies. It's also important to know how to create your own modules for code that you frequently reuse across multiple projects. What you'll learn--and how you can apply it Learn how to install npm and use it to install Node modules. Also learn how to search for existing Node modules and create and publish your own. This lesson is for you because ... You're new to Node. You've installed it, and played around with the core Node modules, but you need to take advantage of functionality from other, third-party modules Prerequisites Basic experience with Node.js Materials or downloads needed in advance None